2017
DOI: 10.1016/j.jeurceramsoc.2017.04.045
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the piezoelectric properties in potassium-sodium niobate-based lead-free piezoceramics: Interrelationship between intrinsic and extrinsic factors

Abstract: Lead zirconate titanate (PZT) based ceramics are currently enjoying a wide use in piezoelectric devices despite lead toxicity. Due to growing environmental concerns, the attention on piezoelectric ceramics has been moving to lead-free materials, in particular to (K,Na)NbO 3-based ceramics. Here we report a systematic evaluation of the effects of the compositional modifications on [(K0.44Na0.52Li0.04)[(Nb0.86Ta0.10Sb0.04)1-xZr5x/4]O3 lead-free piezoceramics. We show that an interrelationship between the intrins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(49 citation statements)
references
References 60 publications
2
45
0
Order By: Relevance
“…Indeed, as x increases, the mean grain size also increases from 1.37 μm ( x = 0) to 2.32 μm ( x = 0.2), and then decreases to 0.22 μm ( x = 0.8) (Figure E‐H). Previous studies reported that an increase in grain size can improve the ferro/piezoelectric properties, and that a reduced grain size can strengthen the coupling effect between grains and grain boundaries, which hinders switching of the domains . In this work, an easy domain switching is clearly observed in ceramics with x = 0.2 (Figure ), due to the R‐T phase boundary and the addition of La 3+ .…”
Section: Resultssupporting
confidence: 49%
See 1 more Smart Citation
“…Indeed, as x increases, the mean grain size also increases from 1.37 μm ( x = 0) to 2.32 μm ( x = 0.2), and then decreases to 0.22 μm ( x = 0.8) (Figure E‐H). Previous studies reported that an increase in grain size can improve the ferro/piezoelectric properties, and that a reduced grain size can strengthen the coupling effect between grains and grain boundaries, which hinders switching of the domains . In this work, an easy domain switching is clearly observed in ceramics with x = 0.2 (Figure ), due to the R‐T phase boundary and the addition of La 3+ .…”
Section: Resultssupporting
confidence: 49%
“…Previous studies reported that an increase in grain size can improve the ferro/piezoelectric properties, and that a reduced grain size can strengthen the coupling effect between grains and grain boundaries, which hinders switching of the domains. 37 In this work, an easy domain switching is clearly observed in ceramics with x = 0.2 (Figure 7), due to the R-T phase boundary and the addition of La 3+ . Therefore, the fatigue-free behavior in these ceramics is mainly attributed to the dense microstructure and easy domain switching.…”
Section: Et Almentioning
confidence: 50%
“…The ε r value exhibited an increasing trend first and then decreased when x ≥ 0.008, while the dielectric loss showed the opposite trend. For piezoelectric ceramics, both the intrinsic polarization rotation and the extrinsic domain wall contribution contributed to the piezoelectric response . In general, samples with O‐T coexisting phases that possess a high T‐phase fraction demonstrate a high piezoelectric performance due to the large lattice distortion in the T phase.…”
Section: Resultsmentioning
confidence: 99%
“…For piezoelectric ceramics, both the intrinsic polarization rotation and the extrinsic domain wall contribution contributed to the piezoelectric response. 30 In general, samples with O-T coexisting phases that possess a high T-phase fraction demonstrate a high piezoelectric performance due to the large lattice distortion in the T phase. In this study, the gradual shift of T O-T induced by the incorporation of LaFeO 3 could partially contribute to the enhanced d 33 or k p when x ≤ 0.006, while the drastic decrease in the piezoelectric performance with x ≥ 0.008 was ascribed to the phase transition to a pseudocubic phase.…”
Section: Resultsmentioning
confidence: 99%
“…It is difficult to find the lead‐free piezoelectric ceramics with real “MPB” which always leads to optimized temperature stability of electrical properties. Poor temperature stability of lead‐free piezoceramics is almost attributed to the characteristics of polymorphic phase boundary . Fortunately, Zuo et al claimed that MPB can be constructed in NaNbO 3 ceramics by chemical modifications, which benefits the enhancement of piezoelectricity and temperature stability .…”
Section: Introductionmentioning
confidence: 99%